Effect of Minerals on Markers of Risk of Pre-Eclampsia in Pregnant Women: A Hospital Based Study - Ranjit S. Ambad1 , Roshan Kumar Jha2 , Nandkishor Bankar3, Brij Raj Singh4 , Deepti Shrivastava5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Pregnancy specific complication characterised by hypertension, proteinuria, after 20 weeksof the gestation, and along with various signs of damage to organ systems, haemolysis, elevated levels ofliver enzymes and low platelet count (HELLP syndrome) is collectively termed as eclampsia.Method: Cross-sectional study with 3 groups of pregnant women, were taken followed by inclusion andexclusion criteria for characterisation. The study was approved by ethical board of DMIMSU. Mineralsand their relationship were estimated using different method. Preeclamptic group with and withoutsupplementation and pregnant women without preeclampsia were included in the study. Significantdifferences were seen in Na+, K+, Ca, Mg, Se, and Mn when compared with each group.Result and Observation: The levels of K were increased significantly (P < 0.001) in pre-eclamptic groupas compared to control group. There was significant change in levels of Mn when pre-eclamptic groupwas compared to control. Mn was also found to decrease significantly (P < 0.001) in cases as compared tocontrol. However, the levels of Se, Mg, Ca and Na between cases and control were not highly significant. Insupplementation and without supplementation group, Significant differences were seen in levels of Na, K,Ca and very significant difference was seen in levels of Mn. (p<0.0001).Conclusion: Pre-eclamptic pregnant women have higher levels of serum potassium and our finding on Mn,an essential trace mineral, provides new insight into a potentially modifiable way to prevent preeclampsia.In multi-ethnic, predominantly urban and low-income pregnant women high level of Mn is associated withpre-eclampsia.